Long-term prognosis of complete percutaneous coronary revascularisation in patients with diabetes with multivessel disease. Issue 15 (16th April 2015) - Jiménez-Navarro, Manuel F; López-Jiménez, Francisco; Barsness, Gregory; Lennon, Ryan J; Sandhu, Gurpreet S; Prasad, Abhiram
Abstract : Objective: There is a paucity of data on the impact of complete revascularisation (CR) following percutaneous coronary intervention (PCI) among patients with diabetes with multivessel coronary disease. In this study, we assess the impact of CR, using a relatively simple anatomical definition, on long-term outcomes (median follow-up 7.9 years) in patients with diabetes, and compare with patients without diabetes. Methods: 5350 patients with multivessel disease (coronary stenoses ≥70% in ≥2 major epicardial arteries) who underwent PCI between January 1997 and June 2011 were included. Patients were divided into 4 groups according to diabetes and CR status (absence of residual coronary stenosis in major, predominantly proximal, epicardial segments according to Coronary Artery Surgery Study (CASS) classification). Results: Patients with diabetes and patients with incomplete revascularisation (IR) had more adverse clinical and angiographic characteristics. IR was frequent in patients with diabetes, and was marginally more common than in patients without diabetes (47% vs 44%, p<0.001). Patients with diabetes and patients without diabetes had higher mortality rates after IR than after CR (HR 1.56 (95% CI (1.39 to 1.85), p<0.001 for patients with diabetes and 1.70 (95% CI (1.50 to 1.92), p<0.001) in patients without diabetes). However, the absolute risk was higher for patients with diabetes (5-year mortality: IR 35.8%, CR 21.2%) than in patients without diabetes (5-year mortality: IR 22.2%, CR 14.1%). In a multivariable model, IR and diabetes mellitus were independent predictors of total mortality. This effect was present in the bare metal stent and drug-eluting stent eras and in patients with stable disease and acute coronary syndromes. Conclusions: CR is associated with lower long-term mortality in patients with diabetes and patients without diabetes. However the difference was significantly greater in patients with diabetes compared with patients without diabetes.